Understanding the effects of electrode inhomogeneity and electrochemical heterogeneity on pitting corrosion initiation on bare electrode surfaces - Tan, Yongjun (Pergammon, 2011)
The effects of electrode inhomogeneity (EI) and electrochemical heterogeneity (EH) on pitting corrosion initiation have been analysed by revisiting research findings reported in the literature and experimental evidences obtained in our laboratories using the wire beam electrode (WBE) method. Two mechanisms of pitting corrosion initiation have been identified on bare metal surfaces exposed directly to electrolytes. For WBE surface under free corrosion or low anodic polarisation conditions the initiation of pitting corrosion was found to be due to the disappearance of minor anodes, leading to accelerated dissolution of a few remaining major anodes. The nucleation stage of pitting corrosion appeared to be controlled by EI, while the propagation stage appeared to be determined by EH. For WBE surface under large anodic polarisation the initiation of pitting corrosion was found to be due to the formation of active new anodic sites, which is in agreement with the conventional mechanism of pitting nucleation.